THE IMPORTANCE OF ASSISTANT IN ECONOMIC EMPOWERMENT BASED ON BUSINESS ASSISTANCE: CASE STUDY ON WAHANA VISI INDONESIA ADP ECONOMIC PROGRAM, JATINEGARA - Bangun Kuncoro Haryo Aryanto; Fitriyah Fitriyah (Politeknik Kesejahteraan Sosial Bandung, 2019)
This paper discusses that one way to overcome poverty is by effective economic development. Economic development with a charitable nuance is only a short-term solution and it is feared that it cannot sustainably overcome poverty. Therefore, an inclusive empowerment process is needed, one of which is an economic empowerment program by WVI in the form of economic assistance to present the independence of the community with small and medium enterprises. Through a qualitative study in this paper researchers tries to provide an overview of the role of assistant in empowerment activities. In empowerment, assistant acts as a change agent. There are three things that make WVI as an assistant play an important role in empowerment. Assistant have a role as enablers where they enable change by placing the community as the subject of change. The assistant also plays a role in improving business competence. Lastly, to create sustainable conditions, the assistant needs to initiate the formation of a social system in the community as a vehicle for independent problem solving.